Comparison of Social Studies Learning Outcomes Using Documentary Video Media for Grade VIII Students at SMP Negeri 1 Banawa - Hikma, Hikma; Nuraedah, Nuraedah; Misnah, Misnah; Iskandar, Iskandar (Journal of English Language and Education, 2025)
This study aims to answer the following question: "Can the use of documentary videos in social studies learning improve social studies learning outcomes of grade VIII students at SMP Negeri I Banawa?" The main purpose of this study is to find out whether grade VIII students at SMP Negeri 01 Banawa can improve their learning capacity through the use of documentary videos. The study used a pretest-posttest experimental design with a control group and a quasi-experimental approach. The basic random sampling method is used to obtain the sample. All 120 grade VIII students at SMP Negeri 1 Banawa were considered for this study. Thirty students from class VIII B became an experimental group that watched a documentary; thirty students from class VIII D became a control group that did not watch the documentary. Multiple-choice exams containing 20 questions designed to measure students' progress in history and geography lessons are used as research instruments. Statistical analysis, i.e. t-test in Excel, is used to analyze the data obtained from exam instruments. Based on the findings of the study, the null hypothesis is rejected and an alternative hypothesis is accepted when the resulting values are greater than 2,366 and 2,003, respectively, at a significance level (α) of 0.05. This shows that grade VIII students at SMP Negeri 1 Banawa can benefit from the use of documentary videos in the classroom.